Length‐Dependent Charge Generation from Vertical Arrays of High‐Aspect‐Ratio ZnO Nanowires. Issue 43 (11th September 2013) - Rivera, Vivian Farías; Auras, Florian; Motto, Paolo; Stassi, Stefano; Canavese, Giancarlo; Celasco, Edvige; Bein, Thomas; Onida, Barbara; Cauda, Valentina
Abstract Aqueous chemical growth of zinc oxide nanowires is a flexible and effective approach to obtain dense arrays of vertically oriented nanostructures with high aspect ratio. Herein we present a systematic study of the different synthesis parameters that influence the ZnO seed layer and thus the resulting morphological features of the free‐standing vertically oriented ZnO nanowires. We obtained a homogeneous coverage of transparent conductive substrates with high‐aspect‐ratio nanowire arrays (length/diameter ratio of up to 52). Such nanostructured vertical arrays were examined to assess their electric and piezoelectric properties, and showed an electric charge generation upon mechanical compressive stress. The principle of energy harvesting with these nanostructured ZnO arrays was demonstrated by connecting them to an electronic charge amplifier and storing the generated charge in a series of capacitors. We found that the generated charge and the electrical behavior of the ZnO nanowires are strictly dependent on the nanowire length. We have shown the importance of controlling the morphological properties of such ZnO nanostructures for optimizing a nanogenerator device.